Superoxide induced deprotection of 1,3-dithiolanes: A convenient method of dedithioacetalization - Shukla A.K.; Verma M.; Singh K.N. (My University, 2025)
Tetraethylammonium superoxide, generated in situ by the phase transfer reaction of potassium superoxide and tetra-ethylammonium bromide, brings about an easy deprotection of a variety of 1,3-dithiolanes of carbonyl compounds under significantly mild reaction conditions at room temperature.